2010
DOI: 10.1371/journal.pone.0013745
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Evidence for Inhibition of Bacterial Division Protein FtsZ by Berberine

Abstract: BackgroundBerberine is a plant alkaloid that is widely used as an anti-infective in traditional medicine. Escherichia coli exposed to berberine form filaments, suggesting an antibacterial mechanism that involves inhibition of cell division. Berberine is a DNA ligand and may induce filamentation through induction of the SOS response. Also, there is biochemical evidence for berberine inhibition of the cell division protein FtsZ. Here we aimed to assess possible berberine mechanism(s) of action in growing bacteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
109
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 174 publications
(112 citation statements)
references
References 48 publications
2
109
0
1
Order By: Relevance
“…It has been reported that isoquinoline such as chelerythrine possess two mechanisms in inhibiting the growth of bacterial cells; through inhibiting the cellular division and nucleic acid synthesis. Isoquinoline inhibits cellular division by tampering with the FtsZ protein, a protein which is essential for the Z ring formation during cellular division [98][99]. In addition, the synthesis of nucleic acids is also inhibited as isoquinoline inhibits the action of type I topoisomerases; this prevents the translation of antibiotic resistant genes, increasing bacterial susceptibility towards antibiotics [100].…”
Section: Alkaloidsmentioning
confidence: 99%
“…It has been reported that isoquinoline such as chelerythrine possess two mechanisms in inhibiting the growth of bacterial cells; through inhibiting the cellular division and nucleic acid synthesis. Isoquinoline inhibits cellular division by tampering with the FtsZ protein, a protein which is essential for the Z ring formation during cellular division [98][99]. In addition, the synthesis of nucleic acids is also inhibited as isoquinoline inhibits the action of type I topoisomerases; this prevents the translation of antibiotic resistant genes, increasing bacterial susceptibility towards antibiotics [100].…”
Section: Alkaloidsmentioning
confidence: 99%
“…FtsZ is a well-studied member of this family of proteins; at nonpermissive temperatures, ftsZ mutants of Escherichia coli are incapable of cellular division (4,9,10,33,56). Likewise, hydrostatic pressure, the SOS response via SulA, and antimicrobials, such as berberine and cinnamaldehyde, induce filamentation of E. coli by preventing the polymerization of FtsZ (5,12,13,24,30,39,55). ␀-Lactam antibiotics that bind penicillin-binding protein 3 (PBP3, also known as FtsI) inhibit its enzymatic activity and septum formation but not cellular growth (46,62).…”
mentioning
confidence: 99%
“…12 The isoquinolines perturbate of the Z-ring and inhibition cell division. 13,14 The quinolones, which is lack of the 3-carboxyl group, unable to inhibit the type II topoisomerase enzymes (Heeb). 15 Agelasines inhibit BCG 3185c enzyme, a suspected dioxygenase which thereby allows disruption of bacterial homeostasis.…”
Section: Resultsmentioning
confidence: 99%